(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Green Marketing is the popular expression of organizations and quiet dominatingly obvious in their marketing map and in the meantime how beneficial these organizations make out of is the essence in consistently changing energetic markets to suit rapidly blurring consumer inclinations. This paper analyzes the pertinence of Green Marketing in the present setting with unique reference to Indian conditions keeping the natural issues and practical advancement both as key spaces for a gainful business age. The paper is essentially an applied one in nature.